Solve for a square root of a-1=3

Math
a-1=3
To remove the radical on the left side of the equation, square both sides of the equation.
a-12=32
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in ((a-1)12)2.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
(a-1)12⋅2=32
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
(a-1)12⋅2=32
Rewrite the expression.
(a-1)1=32
(a-1)1=32
(a-1)1=32
Simplify.
a-1=32
Raise 3 to the power of 2.
a-1=9
a-1=9
Move all terms not containing a to the right side of the equation.
Tap for more steps…
Add 1 to both sides of the equation.
a=9+1
Add 9 and 1.
a=10
a=10
Solve for a square root of a-1=3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top